The Effects of Shock Size and Type on Labor‐Contract Duration - Wallace, Frederick H. (Journal of Labor Economics, 2001)
Empirical studies of the relation between uncertainty and the length of union‐firm contracts have focused on the effects of inflation, money‐supply, or industry‐specific uncertainty. This article describes two extensions of previous work. First, real, aggregate uncertainty arising from oil shocks is incorporated into a contract‐duration model. Oil shocks significantly affect contract length in seven of 21 U.S. manufacturing industries. Second, the model is used to test whether the duration of reopenable bargains is positively related to uncertainty associated with large shocks, as has been described in Danziger. The evidence indicates some qualified support for this proposition.